Penerapan Pembelajaran Berdiferensiasi Terhadap Hasil Belajar Siswa Pokok Bahasan Cahaya Kelas VIII SMP - Peni Alis Wijayanti; Arini Rosa Sinensis; Diana Novitasari (U-Teach: Journal Education of Young Physics Teacher, 2023)
This study aims to 1) explore how applying differentiated learning methods affects students' learning outcomes, 2) analyze the impact of differentiated learning on student learning outcomes, and 3) determine the impact of implementing differentiated learning on student learning outcomes. This study was conducted with a unique group pretest and posttest design. This study uses pre-treatment testing and post-treatment testing. Data collection in this study was carried out using a test in the form of an experiment. Differentiated learning is applied based on the student's learning style. Visual learning style uses images, auditory learning style uses audio from learning videos, and kinesthetic learning style uses simple training. After applying the differentiated learning method, learning results increased by 38.39% with an N-Gain value of 0.67, showing that the criteria are moderate and applied effectively for students. Based on the hypothesis testing results from the conducted study, P<0.001 was obtained with an effect size of 2.28, indicating a broad classification. Thus, the implementation of differentiated teaching has impacted and influenced the learning outcomes of students specializing in lighting in grade VIII SMP